Combination of morphological feature analysis and immunohistochemistry is useful for screening of EML4-ALK-positive lung adenocarcinoma. Issue 12 (9th October 2010) - Jokoji, Ryu; Yamasaki, Takashi; Minami, Seigo; Komuta, Kiyoshi; Sakamaki, Yasushi; Takeuchi, Kengo; Tsujimoto, Masahiko
Abstract : Background: A subset of lung cancers harbours the fusion gene echinoderm microtubule-associated protein-like-4–anaplastic lymphoma kinase (EML4-ALK). Recently, immunohistochemistry for ALK has shown sensitivity for the detection of EML4-ALK-positive lung adenocarcinoma almost equal to that of the fluorescence in situ hybridisation (FISH) assay. Aims: To study the clinicopathological features of EML4-ALK-positive lung adenocarcinoma in a large number of surgically resected samples using immunohistochemistry, in order to establish a useful screening method for EML4-ALK-positive lung adenocarcinoma. Methods: Immunohistochemistry for ALK was used to screen for EML4-ALK-positive lung adenocarcinomas in 254 cases of surgically resected samples. Results: EML4-ALK-positive cases were detected in 3.1% of lung adenocarcinomas (8/254). EML4-ALK-positive lung adenocarcinomas showed significant associations with intra- and/or extra-cytoplasmic mucin (p=0.0001), and cribriform pattern with excessive extracytoplasmic mucin (p<0.0001). Signet-ring cell appearance alone lacked significance (p=0.149). Conclusion: EML4-ALK-positive lung adenocarcinoma has a tendency to express a characteristic morphological pattern. The combined use of morphological feature analysis and immunohistochemistry may be a useful and cost effective screening method for EML4-ALK lung adenocarcinoma.